2010
DOI: 10.1590/s0066-782x2010000100021
|View full text |Cite
|
Sign up to set email alerts
|

Alterações ecocardiográficas em pacientes com insuficiência renal crônica em programa de hemodiálise

Abstract: Changes in cardiac structure and function detected by echocardiography are common in patients with chronic kidney disease undergoing hemodialysis, and have been recognized as key outcome predictors. This review attempts to summarize recent evidence pointing to the usefulness of the method in the detection of clinical and subclinical cardiac dysfunction, stratification of cardiovascular risk and assessment of intervention strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
10

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 67 publications
1
8
0
10
Order By: Relevance
“…We observed a high prevalence of LVH, whether correcting for body surface area (67.5%), or by height (72.5%) at baseline examination prior to kidney transplantation in this study, which is in agreement with literature data demonstrating a prevalence of LVH ranging from 60% to 70% in patients that start dialysis 18 . There was also a decrease in the prevalence of LVH six months after the transplantation, but without statistical significance when compared to baseline assessment.…”
Section: Discussionsupporting
confidence: 92%
“…We observed a high prevalence of LVH, whether correcting for body surface area (67.5%), or by height (72.5%) at baseline examination prior to kidney transplantation in this study, which is in agreement with literature data demonstrating a prevalence of LVH ranging from 60% to 70% in patients that start dialysis 18 . There was also a decrease in the prevalence of LVH six months after the transplantation, but without statistical significance when compared to baseline assessment.…”
Section: Discussionsupporting
confidence: 92%
“…LAV is a potentially useful parameter to assess diastolic dysfunction and is related to the severity and duration of the dysfunction 5 . In a study of a population on renal replacement therapy, Barberato et al 33 showed that LAVI was a predictor of mortality.…”
Section: Survival Function Censoredmentioning
confidence: 99%
“…Studies carried out in hemodialysis patients showed that the prevalence of diastolic dysfunction in this population can vary from 63.5% to 87%, depending on the criteria used for definition and patients included in the sample [36][37][38] . Diastolic dysfunction is characterized by alterations in ventricular relaxation and compliance 5 and its high prevalence can be explained by the fact that the CKD expose the heart to pressure and volume overload and associated hemodynamic factors that cause myocardial alterations 39 . Myocardial fibrosis resulting from these processes is a major determinant of LV stiffness and elevated filling pressures, predisposing to the development of diastolic dysfunction 39 .…”
Section: Siqueira Et Al Doppler Echocardiogram In Hemodialysis Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alterações morfofisiológicas do ventrículo esquerdo (como hipertrofia, dilatação e disfunção sistólica) são comuns em pacientes com insuficiência renal crônica e predizem pior prognóstico 1 . Diretrizes norte-americanas recomendam o eco para todos os pacientes de diálise de um a três meses após início da terapia renal substitutiva e em intervalos de três anos, subsequentemente, a despeito dos sintomas 2 .…”
Section: -Insuficiência Renal Crônicaunclassified